Pengaruh Kecanduan Game online Mobile Legends Terhadap Prestasi Akademik Siswa - Rahmayanti, Hanna; Nurmala, Meilla Dwi; Handoyo, Alfiandy Warih (Prodi Bimbingan dan Konseling Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2024)
This research aims to find out a general picture of the influence of online game addiction on grade 11 students at SMK PGRI 1 Serang City. This type of research uses quantitative research with sampling using saturated sampling techniques with a sample size of 144 students. The measuring tool used in this research is a Likert scale with aspects of online game addiction. The data analysis technique uses quantitative correlation. The research results show that the results of research data on the influence of online game addiction on students' academic achievement in class 11 of SMK PGRI 1 Serang City obtained correlation analysis results of r = -0.447 with a significance value of 0.000 < 0.05. These results show that there is an influence between the online game addiction variable and the achievement variable. . This shows that the role of online game addiction on academic achievement is 0.198, meaning that the influence of online game addiction on academic achievement is 19.8% and 80.2% is influenced by external factors in this study.